MANIFESTATION OF PERSON'S SOCIAL-PSYCHOLOGICAL ATTITUDES IN MANAGEMENT - Petrosyan , L.H. (Modern Psychology, 2021)
Psychological science proves that a person can use his potential to the fullest if he works in a field compatible with his personal characteristics and working attitudes. This fact has been recently the focus of the management, in particular, in the process of developing human resource management strategies. The process of person-position matching requires not only managerial approaches, but also psychological ones. We set a task of studying a person's social-psychological attitudes in working activities in a transforming society. The method of diagnostics of social and psychological attitudes of the personality by O.F. Potyomkina was selected for the research. The research group consisted of the managers of different levels with 5-20 years of work experience (n = 860) who have higher education, and work in a private organizations. The results of the research showed that the group was more oriented towards freedom, result and altruism. The indicators of the orientation to the money and power were less pronounced. It turns out that material motivations in this group can not affect the quality of the work even in case of the high performance rates. While conducting this research, the problem was raised to study the differences in the social-psychological attitudes of managers and non-managers at work. Only in the case of one criterion (orientation towards power) the indicators of the social-psychological attitudes of managers and non-managers were different, which indicates that non-managers are less oriented towards power than those who hold managerial positions.
Keywords: personality; research; psychological attitudes; professional development